Analysis of the Behavior of a Chaotic Dynamic System under Different Types of Couplings and Several free Dynamics - Grácio, Clara; Fernandes, Sara; Lopes, Luís; Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2019)
In this paper, we analyze how the behavior of a chaotic dynamical system changes when we couple it with another. We focus our attention on two aspects: the possibility of chaos suppression and the possibility of synchronization. We consider a Symmetric Linear Coupling and several free dynamics. For each of them we study the evolution of the coupling behavior with the coupling strength constant, defining windows of behavior. We extend the analysis to some other couplings. This is a survey paper.